Jejak-Jejak Siwa Siddhanta dan Penerapan Ajarannya Pada Masyarakat Hindu Nusantara - I Made Girinata (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The source of the teachings of Hinduism is the Vedic scriptures. All Hindu teachings breathe Veda, although they appear in other forms. The Vedas animate the teachings of Hinduism. Therefore Hinduism recognizes the truth and believes in the teachings of the Vedic scriptures. In Wrhaspati Tattwa Shivaistics is also taught including: cetana, acetana, siwatattwa, sadasiwatattwa, paramasiwatattwa, cadu sakti, tri Guna tattwa, atma, janggama, sthavara, astasiddhi, dasa prana, panca pada, paramartha, moksa, dasa sila, and siva. asta aiswarya. The Tattwa Jnana includes: cetanma, acetana, Shiva tattwa, maya tattwa, cadu sakti, purusa, pradhana, tri Guna, citta, buddhi, ahangkara, dasa indriya, five tanmatra, five maha bhuta, andha bhuwana, sapta bhuwana, sapta bhuwana, sapta bhuwana, , Sapta Parwata, Sapta Arnawa, Sapta Dwipa, Panca Wayu, Wayu, Words of Idep, Tri Pramana, Manah, Atma, Five Atma, Atma Wisesa, Tapa, Brata, Yoga, and Samadhi. The essence of philosophical teachings on the source of Shiva Siddhanta is explained, that Shiva is the highest reality of the soul or personal spirit which is of the same essence as Shiva, but not identical. Pati (God), Pasu (spirit), and Pasa (binder) and the 36 tattwa or principles that make up the universe are all real